Terpenes and Terpenoids (IntechOpen, 2023)
Terpenes belong to the diverse class of chemical constituents isolated from materials found in nature. They play a very important role in human health and have significant biological activities, including anticancer, antimicrobial, anti-inflammatory, and antioxidant effects. This book provides an overview and highlights recent research in the phytochemical and biological understanding of terpenes and terpenoids, examining the most essential functions of these kinds of secondary metabolites.